2020
DOI: 10.1101/2020.01.08.899492
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the polyamine synthesis enzyme ornithine decarboxylase sensitizes triple-negative breast cancer cells to cytotoxic chemotherapy

Abstract: Treatment of triple-negative breast cancer (TNBC) is limited by a lack of effective molecular targeted therapies. Recent studies have identified metabolic alterations in cancer cells that can be targeted to improve responses to standard-of-care chemotherapy regimens. We found that exposure of TNBC cells to cytotoxic chemotherapy drugs leads to alterations in arginine and polyamine metabolites due to a reduction in the levels and activity of a rate-limiting polyamine biosynthetic enzyme ornithine decarboxylase … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(75 reference statements)
1
4
0
Order By: Relevance
“…Recently, Geck et al. noticed that DFMO treatment sensitized TNBC cells to chemotherapy because ODC levels were elevated in TNBC patient samples ( 17 ), and this reason could be also true in our work. An additional possibility is that the A 1 AR signaling pathway in TNBC is also up-regulated.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Recently, Geck et al. noticed that DFMO treatment sensitized TNBC cells to chemotherapy because ODC levels were elevated in TNBC patient samples ( 17 ), and this reason could be also true in our work. An additional possibility is that the A 1 AR signaling pathway in TNBC is also up-regulated.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies found that ODC is often oncogene-driven and a bona fide drug target ( 13 , 14 ). The expression level of ODC and the polyamine concentration are significantly up-regulated in breast cancer cells, and inhibiting ODC is an attracting option for treating breast cancer ( 15 17 ). One of the best known ODC inhibitor is DFMO ( α -difluoromethylornithine), which has been intensively tested in many clinical trials for treating cancers ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines have various biological functions, such as antioxidation, free radical scavenging, and intracellular calcium regulation, all of which reportedly have an impact on hearing [50,51]. Accumulating evidence shows that ornithine decarboxylase is associated with disordered cell growth regulation [52][53][54]. Aside from this pathway, PI metabolism had not been reported to be associated with ARHI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies into the molecular biology underlying breast cancer have found that polyamines, organic molecules that play a large role in eukaryotic cell growth and development, have elevated amounts in breast cancer tissue [7][8][9]. Polyamines control gene expression at transcriptional, posttranscriptional, and translational levels, modulating functions of DNA, nucleotide triphosphates, RNA, and proteins [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…While inhibition of polyamines through the ornithine decarboxylase enzyme has been shown to provide protection against breast cancer [9,26], it is not known whether this would be true for diabetes-linked cancer advancement as well. In fact, polyamine pathway can be a potential target to treat chemoresistance in triple negative breast cancer [9,27]. Thus, we hypothesized that high glucose (HG) conditions advance breast cancer cell proliferation, with a possible role of polyamine pathway.…”
Section: Introductionmentioning
confidence: 99%